Impedance and dielectric properties of mercury cuprate at nonsuperconducting state - Ozdemir, Z. Guven; Cataltepe, O. Aslan; Onbasli, U. . (WORLD SCIENTIFIC PUBL CO PTE LTD, 2015)
In this paper, impedance and dielectric properties of nonsuperconducting state of the mercury-based cuprate have been investigated by impedance measurements within the frequency interval of 10 Hz-10 MHz for the first time. The dielectric loss factor (tg delta) and ac conductivity (sigma(ac)) parameters have also been calculated for non-superconducting state. According to impedance spectroscopy analysis, the equivalent circuit of the mercury cuprate system manifests itself as a semicircle in the Nyquist plot that corresponds to parallel connected resistance-capacitance circuit. The oscillation frequency of the circuit has been determined as approximately 45 kHz which coincides with the low frequency radio waves. Moreover, it has been revealed that the mercury-based cuprate investigated has high dielectric constants and hence it may be utilized in microelectronic industry such as capacitors, memory devices etc., at room temperature. In addition, negative capacitance (NC) effect has been observed for the mercury cuprate regardless of the operating temperatures at nonsuperconducting state. Referring to dispersions in dielectric properties, the main contribution to dielectric response of the system has been suggested as dipolar and interfacial polarization mechanisms.
Keywords: Superconductors; electronic characterization; dielectric properties; electrical conductivity; NEGATIVE CAPACITANCE; TRANSPORT-PROPERTIES; SUPERCONDUCTIVITY; TEMPERATURE; PHASE; CONSTANT; Physics